2020
DOI: 10.1186/s12866-020-01777-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different drugs and drug combinations on killing stationary phase and biofilms recovered cells of Bartonella henselae in vitro

Abstract: Background: Bartonella henselae is a Gram-negative bacterium transmitted to humans by a scratch from cat in the presence of ectoparasites. Humans infected with B. henselae can result in various clinical diseases including local lymphadenopathy and more serious systemic disease such as persistent bacteremia and endocarditis. The current treatment of persistent B. henselae infections is not very effective and remains a challenge. To find more effective treatments for persistent and biofilm Bartonella infections,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 35 publications
(49 reference statements)
1
38
0
Order By: Relevance
“…Resistance to standard treatments has been reported for both Babesia and Bartonella spp. [ 69 , 70 ], and resistant biofilm and persister forms have also recently been reported for Bartonella [ 132 , 133 ]. Would addressing Babesia and/or Bartonella with newer medication regimens, including tafenoquine for Babesia [ 134 ] and/or novel combination therapies for Bartonella (i.e., macrodantin, rifampin, methylene blue, gentamycin with essential oils) [ 133 ], prior to DDD CT improve clinical outcomes in co-infected patients?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to standard treatments has been reported for both Babesia and Bartonella spp. [ 69 , 70 ], and resistant biofilm and persister forms have also recently been reported for Bartonella [ 132 , 133 ]. Would addressing Babesia and/or Bartonella with newer medication regimens, including tafenoquine for Babesia [ 134 ] and/or novel combination therapies for Bartonella (i.e., macrodantin, rifampin, methylene blue, gentamycin with essential oils) [ 133 ], prior to DDD CT improve clinical outcomes in co-infected patients?…”
Section: Discussionmentioning
confidence: 99%
“…[ 69 , 70 ], and resistant biofilm and persister forms have also recently been reported for Bartonella [ 132 , 133 ]. Would addressing Babesia and/or Bartonella with newer medication regimens, including tafenoquine for Babesia [ 134 ] and/or novel combination therapies for Bartonella (i.e., macrodantin, rifampin, methylene blue, gentamycin with essential oils) [ 133 ], prior to DDD CT improve clinical outcomes in co-infected patients? Similarly, the three biofilm agents (Stevia, oregano oil, Biocidin) we used in our study were all found to have efficacy against biofilms and morphological forms of Borrelia [ 33 , 34 , 104 ], but would other biofilm agents or combinations against Borrelia and/or associated co-infections be more efficacious [ 33 , 135 ]?…”
Section: Discussionmentioning
confidence: 99%
“…Treatment failure in patients diagnosed with B. henselae endocarditis has been largely attributed to the ability of B. henselae to form a biofilm and resist antibiotics. Recent in vitro data suggests drug combination treatments are more effective in eliminating B. henselae chronic infection, compared to current single drug treatments [ 22 ]. Despite the continued use of antibiotics, systemic cases of B. henselae infection remain difficult to treat and often require more invasive treatment courses [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance of Babesia and Bartonella spp. to standard treatments have both been reported[69] [70] and resistant biofilm and persister forms have also recently been reported for Bartonella[132] [133]. Would addressing Babesia and/or Bartonella with newer medication regimens including tafenoquine for babesia[134] and/or novel combination therapies for Bartonella (i.e., macrodantin, rifampin, methylene blue, gentamycin with essential oils)[133] prior to DDD CT improve clinical outcomes in co-infected patients?…”
mentioning
confidence: 99%
“…to standard treatments have both been reported[69] [70] and resistant biofilm and persister forms have also recently been reported for Bartonella[132] [133]. Would addressing Babesia and/or Bartonella with newer medication regimens including tafenoquine for babesia[134] and/or novel combination therapies for Bartonella (i.e., macrodantin, rifampin, methylene blue, gentamycin with essential oils)[133] prior to DDD CT improve clinical outcomes in co-infected patients? Similarly, the three biofilm agents (Stevia, oregano oil, Biocidin) we used in our study were all published to have efficacy against biofilms and morphological forms of Borrelia[34] [33][104], but would other biofilm agents or combinations against Borrelia and/or associated co-infections be more efficacious[33] [135]?…”
mentioning
confidence: 99%